Relationship Between Pregnancy and Acute Disseminated Encephalomyelitis: A Single-Case Study - Deng, Shuwen; Qiu, Ke; Tu, Ranran; Zheng, Haiping; Lu, Wei (Frontiers in Immunology, 2021)
Abstract The relationships between pregnancy and autoimmune diseases are unclear. This study investigated the possible roles of local immune changes and the activation state of the HMGB1/TLR4/Nf-κB/IL-6 pathway at the maternal–fetal interface during pregnancy in the pathogenesis of acute disseminated encephalomyelitis (ADEM). Clinical data and blood samples of a patient with ADEM were collected to observe the dynamic changes in lymphocyte populations after an abortion. The expression of HMGB1, TLR4, Nf-κB, AQP4, IL-2, IL-4, IL-6, and TNF-α in the fetal membrane and placenta was compared between the patient with pregnancy-related ADEM and a woman with a normal pregnancy using Real-time qPCR and western blotting (WB). The patient was diagnosed with ADEM in the early stage of pregnancy after showing limb weakness symptoms. In the third month of gestation, the symptoms worsened, with a disturbance of consciousness and breathing. After the abortion, the patient relapsed with vertigo and visual rotation. Analysis of lymphocyte subsets by flow cytometry showed that B lymphocytes increased, while natural killer T lymphocytes decreased. WB and Real-time qPCR showed that the expression levels of HMGB1, TLR4, Nf-κB, AQP4, and IL-6 in the fetal membrane and placenta were higher in the patient with pregnancy-related ADEM than in the woman with a normal pregnancy, while those of IL-2 were lower in the patient than in the woman with a normal pregnancy. The local immune changes and the activation of the HMGB1/TLR4/Nf-κB/IL-6 pathway at the maternal–fetal interface may be related to the pathogenesis of ADEM.